The art of the pitch : persuasion and presentation skills that win business - Coughter, Peter (Ascent Audio, 2020)
Through an engaging and humorous narrative, Peter Coughter presents the tools he designed to help advertising and marketing professionals develop persuasive presentations that deliver business. Readers will learn how to develop skills to create the perfect presentation.